Is there sustainable entrepreneurship in the wine industry? Exploring sicilian wineries participating in the SOStain program - Emanuele Schimmenti; Giuseppina Migliore; Caterina Patrizia Di Franco; Valeria Borsellino (Wine Economics and Policy, 2016)
Global climate change and the accelerating depletion of natural resources have contributed to increase discussions about the role of private enterprises in reversing negative environmental trends. Rather than focusing on profit maximization, policy makers and consumers pressure groups expect firms to meet a triple-bottom line of economic, environmental and social value creation. Hence sustainable entrepreneurship has received recently increasing interest as a phenomenon and a research topic. More recently, the concept of sustainability has been taken seriously in the Italian wine industry. The organizational challenge for entrepreneurship is to better integrate social and environmental performance into the economic business logic. The aim of this manuscript is to illustrate, through a descriptive approach, the adaptation of the wine industry to the new scenario of sustainable entrepreneurship. To reach this goal we carried out an explorative analysis of 3 Sicilian wineries involved in the SOStain program, which aims at the improvement of sustainability in the wine industry. The findings of the analysis show the existence of sustainability-driven entrepreneurship, in which the wineries undertake to behave ethically and contribute to economic development while improving the quality of life for the workforce, their families, the local and global community as well as future generations.
Keywords: 330; Management; Sustainability; Winegrowing